2008
DOI: 10.1159/000140961
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative CA19-9 Levels and Lymph Node Ratio Are Independent Predictors of Survival in Patients with Resected Pancreatic Ductal Adenocarcinoma

Abstract: Background: The aim of this study was to identify whether preoperative CA19-9 levels might represent an independent prognostic marker for overall survival in patients undergoing resection for pancreatic ductal adenocarcinoma, and to describe the relationship between CA19-9 and tumour histology. Methods: 109 patients who had a pancreatoduodenectomy for pancreatic ductal adenocarcinoma with recorded preoperative CA19-9 levels were identified from a prospectively maintained database (1997–2006). Multivariate anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 67 publications
(43 reference statements)
3
49
1
1
Order By: Relevance
“…However, clinically there are still no reliable biomarkers for detecting PC, and CA19-9 and CEA are now commonly used to screen and monitor PC, while their sensitivities or specificities are insufficient. CA19-9 is a sialyated Lewis blood group cell surface carbohydrate antigen, expressed in normal pancreatic ductal cells in around 95 % of the population which express the Lewis antigen glycosyltransferase enzyme [15][16][17][18][19][20]. The utility of CA19-9 is limited in patients who are Lewis blood type negative (Lea -b -).…”
Section: Discussionmentioning
confidence: 99%
“…However, clinically there are still no reliable biomarkers for detecting PC, and CA19-9 and CEA are now commonly used to screen and monitor PC, while their sensitivities or specificities are insufficient. CA19-9 is a sialyated Lewis blood group cell surface carbohydrate antigen, expressed in normal pancreatic ductal cells in around 95 % of the population which express the Lewis antigen glycosyltransferase enzyme [15][16][17][18][19][20]. The utility of CA19-9 is limited in patients who are Lewis blood type negative (Lea -b -).…”
Section: Discussionmentioning
confidence: 99%
“…In summary, these studies suggest that a median CA 19-9 serum level <100 U/ml correlates with resectability (41-80%) whereas levels >100 U/ml suggest advanced or metastatic pancreatic cancer (60-85%) (Table 3). The utility of serum CA 19-9 levels to provide meaningful prognostic information and permit patient stratification (survival groups) based on CA 19-9 serum level has been extensively evaluated [22,24,26,30,31,[36][37][38][39][40][41][42][43][44][45][46][47][48][49] (Table 4). Waraya et al performed a multivariate analysis of factors predicting survival in 117 pancreatic cancer patients undergoing surgical resection and reported that a low preoperative CA 19-9 serum levels (28-30 U/ml) (p<0.0016, relative risk (RR), 2.16) and positive peripancreatic margin (p<0.04, RR, 1.62) independently predicted survival [46].…”
Section: Ca 19-9: Introductionmentioning
confidence: 99%
“…U/ml unit/milliliter, SD standard deviation, NA not available, R0 resection-microscopic margin tumor free, R1 resection-microscopic margins positive for tumor, R2 resection-macroscopic tumor left behind Author, Year N= CA 19-9 cut-off levels (U/ml) Median survival (months) 4 months in patients with a preoperative CA19-9 level >150 U/ml (N=64), compared to a median survival of 22.1 months in patients with a CA19-9 serum level ≤150 U/ml (N=45, p<0.012) [45]. Table 3 lists additional studies which have used various cut-off levels for pre-operative CA 19-9 serum levels in an effort to predict survival among pancreatic cancer patients [22,24,26,30,31,[36][37][38][39][40][41][42][43][44][45][46][47][48][49]. These studies support the conclusion that a normal (<37 U/ml) or low preoperative CA 19-9 serum level (<100 U/ml) correlates with early pancreatic cancer stage and independently predicts improved overall survival, whereas an elevated CA 19-9 serum levels (>100 U/ml) is associated with a poor prognosis.…”
Section: Ca 19-9: Introductionmentioning
confidence: 99%
“…Correlations were also examined between CK18 and the circulating levels of carbohydrate antigen 19-9 (CA19-9), the only widely used biomarker in pancreatic cancer (Smith et al, 2008). Preoperative www.bjcancer.com Molecular Diagnostics biliary stenting and concurrent liver function were also investigated in the interpretation of CK18 levels, as obstructive jaundice has been shown to be a confounding factor in proteomic studies (Yan et al, 2009) along with effect of plasma storage duration (Cummings et al, 2007;Greystoke et al, 2008).…”
mentioning
confidence: 99%